Peningkatan Pengetahuan Masyarakat tentang Pemilahan Sampah untuk Menciptakan Lingkungan Sehat - Faizah Khusnul Haya; Amelia Dewi Saputri; Anas Wibowo Jati; Agus Kharmayana Rubaya; Ibnu Rois; Daryati P. Achmad (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Improper household waste management remains a significant environmental and public health issue, particularly due to the widespread practice of open waste burning. A preliminary survey in Kalijoho Hamlet, Bantul Regency, found that 96% of households still burned their waste because the local waste bank was underutilized. This community service program aimed to improve community knowledge regarding the hazards of open waste burning, household waste segregation, and waste bank utilization. The program was implemented through four stages: problem identification, Community Self-Survey (CSS), educational sessions, and waste segregation training involving housewives and Family Welfare Empowerment (PKK) members. Program effectiveness was evaluated using pre-test and post-test questionnaires and analyzed with the Wilcoxon signed-rank test. The results showed a significant improvement in participants' knowledge, with the mean score increasing from 109.41 to 120.00. Participants also demonstrated improved waste segregation practices and a better understanding of the environmental and economic benefits of waste banks. This program effectively enhanced community knowledge and skills, providing a foundation for sustainable community-based household waste management.